Analisis Potensi Pajak Hotel Dalam Rangka Peningkatan Pajak Daerah Kota Makassar - Wahdah Agustina; Nurul Afifah; Mahardian Hersanti Paramita (Income Journal: Accounting, Management and Economic Research, 2022)
Hotel tax is a tax that is very potential with the development of the tourism sector in Makassar City. The strategic location of Makassar City as a city of trade, service, industry, education, and tourism city can encourage the growth of the hotel industry, directly or indirectly can have an impact on increasing the Regional Tax The purpose of this research is to find out how much the hotel tax potential is actually owned Makassar City and how far the attention of the Makassar City Regional Government is in exploring the potential of existing Hotel Taxes and the form of attention of the Regional Government in increasing Hotel Taxes for mutual benefit. The research method used in this study is quantitative descriptive analysis. To calculate the Hotel Tax potential, several related variables are used, namely the number of rooms, the average room rate, the number of days in a year, the level of room occupancy, and the amount of the Hotel Tax rate that is determined. This research data was obtained from literature studies related to this research. The results of the study indicate that there is a considerable difference between hotel tax potential and the target set by the regional government. The highest level of hotel tax effectiveness occurred in 2013 with a percentage reaching 103.5% and categorized as very effective. While the lowest percentage of hotel tax effectiveness occurred in 2016 with a percentage of 51.0% and categorized as ineffective. This shows that the hotel tax collection system is not optimal.